Exosome-loaded extracellular matrix-mimic hydrogel with anti-inflammatory property Facilitates/promotes growth plate injury repair - Pengfei Guan (KeAi Communications Co., Ltd., 2022)
Growth plate cartilage has limited self-repair ability, leading to poor bone bridge formation post-injury and ultimately limb growth defects in children. The current corrective surgeries are highly invasive, and outcomes can be unpredictable. Following growth plate injury, the direct loss of extracellular matrix (ECM) coupled with further ECM depletion due to the inhibitory effects of inflammation on the cartilage matrix protein greatly hinder chondrocyte regeneration. We designed an exosome (Exo) derived from bone marrow mesenchymal stem cells (BMSCs) loaded ECM-mimic hydrogel to promote cartilage repair by directly supplementing ECM and anti-inflammatory properties. Aldehyde-functionalized chondroitin sulfate (OCS) was introduced into gelatin methacryloyl (GM) to form GMOCS hydrogel. Our results uncovered that GMOCS hydrogel could significantly promote the synthesis of ECM due to the doping of OCS. In addition, the GMOCS-Exos hydrogel could further promote the anabolism of chondrocytes by inhibiting inflammation and ultimately promote growth plate injury repair through ECM remodeling.